Consolidative mediastinal irradiation of malignant lymphoma using active scanning proton beams: clinical outcome and dosimetric comparison - König, Laila; Bougatf, Nina; Hörner-Rieber, Juliane; Chaudhri, Naved Sarwar; Mielke, Thomas; Klüter, Sebastian; Häfner, Matthias; Rieken, Stefan; Haberer, Thomas; Debus, Jürgen; Herfarth, Klaus (Strahlentherapie und Onkologie, 2019)
Current research approaches in lymphoma focus on reduction of therapy-associated long-term side effects. Especially in mediastinal lymphoma, proton beam radiotherapy (PT) may be a promising approach for reducing the dose to organs at risk (OAR).
Gesehen am 21.04.2020